Indications for postoperative radiotherapy in patients with prostate cancer after surgery with positive surgical margins - Kamecki, Krzysztof; Biedka, Marta; Makarewicz, Roman; Siekiera, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Prostate cancer is the second most prevalent cancer among men in Poland. The main methods of radical treatment are radical prostatectomy and radiotherapy. In patients who have been correctly qualified for surgery, a positive surgical margin is always an unexpected and undesirable factor. The aim of this prospective study was to evaluate the incidence of positive margins in more than 100 consecutive patients with prostate cancer undergoing radical prostatectomy. Material and methods: The study included 114 patients aged 44–78 years (mean 61.5 years) who underwent surgery for prostate cancer in stage cT1-3N0/M0 (according to the TNM staging system) in the years 2010-2011 in the Clinical Department of Oncological Urology in the Center of Oncology in Bydgoszcz. Results : The presence of positive surgical margins was found in 45 (39.47%) patients, and in 20 (17.54%) margins were assessed as close (1–2 mm). Among the patients with positive surgical margins about 22% had biochemical recurrence. Among patients with negative surgical margins 13% of pT2c and 12.5% of pT3a had biochemical recurrence. Patients with positive surgical margins, along with patients diagnosed with tumor extending beyond the prostate (pT3a) or invading seminal vesicles (pT3b), are at an increased risk of recurrence and progression, reaching up to 30–50% over 10 years. The risk is 2–4 times higher than in patients without positive operating margins.